Ciclo reprodutivo de Cranioleuca vulpina (Furnariidae), porção norte do Pantanal, Mato Grosso, Brasil - Arruda, Danilo Grangeiro (2012)
Studies focused on the understanding of avian life history involve knowledge of behavior, ecology, evolution, phylogeny and biological population. The various ways of how birds live, promotes the research for explanations and meanings of different patterns and their origin. Cranioleuca vulpina (family Furnariidae), is a resident species that occurs in virtually all national territory. Being only found near water bodies. In the Pantanal this species occurs in evergreen seasonally flood forest, e.g. Cambarazal and Landi. The overall objective of this work is to present information about the natural history of C. vulpina, however to make a clearer we divide this work read in two chapters: the first refers to the detailed descriptions of basic information in the study of reproductive biology such as: nests, eggs, nestlings, nest size, incubation periods and period of nestlings in nests, parental care, habitat use, nesting spot and reproductive period. The objective of Chapter two is to provide estimates of daily survival rates (DSR) and nest survival (NS), in addition to checking the influence of temporal and environmental variables on the TDS and consequently the NS, through a powerful and flexible tool that allows the realisation of these tests: the program Mark. This study was carried out on the farm Retiro Novo, located in Pirizal region (16°22'00" S; 56°17'56" W), part of the municipality of Poconé, Northern Pantanal, Mato Grosso, Brazil. The data were collected in four breeding seasons (2008-2011) between the months of November and May. Nest searching occerred actively occurred in the study area. The nests were marked and numbered with colored plastic tape at a distance of at least 5 m. The nests were visited every three days, registering their status (active or inactive) at the time of the visit. 138 nests were found of C. vulpina, of these only 62 became active (with eggs or nestlings). The other 76 were abandoned. Among the 62, only 12 (19%) were successful during all the breeding seasons, four nests were lost because of flooding in the area, and 46 (75%) nests were preyed upon. Among the active nests, 26 were found in the Cambarazal type and 36 in Landis type forest, along the full length of rainy season in the Pantanal. The brood size ranged from one (n = 3) the two eggs (n = 32). Male and female build the nest and took turns in incubation and care of the nestling. Average incubation time is 16.3 ± 2.1 (n = 22). The nestlings remain in the nest for an average of 16.3 ± 2.9 (n = 08) days, are born with their eyes closed and lack of hackles. After leaving the nest the young stay with the parents at least 30 days. The reproductive period starts in the month of November ending in May, totaling 191 days. The DSR for a nest, based on 62 nests considered in analysis, was 0.93, showing NS of 9%. The most parcimonios model was the one that considers the DSR constant throughout the reproductive season. The DSR does not differ within and between the years, suggesting that there isn't a phase of nest where predation is more evident. So the hypothesis of Skucth did not receive support in this study. The variables, nest height in relation to the ground, plant density in the vicinity of the nest and habit type were present at some of the best models, i.e. Δ values presented AICc ≤ 2.